2019
DOI: 10.1042/bsr20181958
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: The promises of a holistic view of proteins—impact on antibody engineering and drug discovery

Abstract: The reductionist approach is prevalent in biomedical science. However, increasing evidence now shows that biological systems cannot be simply considered as the sum of its parts. With experimental, technological, and computational advances, we can now do more than view parts in isolation, thus we propose that an increasing holistic view (where a protein is investigated as much as a whole as possible) is now timely. To further advocate this, we review and discuss several studies and applications involving allost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 83 publications
0
42
0
Order By: Relevance
“…Thus future allergen-specific IgE studies and engineering of therapeutic IgEs would benefit from analyzing specific IgEs as a whole rather than as a sum of regions or domains. 55 Although we were able to artificially create a more persistent IgE with V-regions that augmented FcεRIa engagement in the rare pertuzumab VH5 IgE (the only of 10 recombinant IgEs we produced), the discovery for such a patient-derived IgE would certainly change the understanding of the role of IgE V-regions in allergy pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus future allergen-specific IgE studies and engineering of therapeutic IgEs would benefit from analyzing specific IgEs as a whole rather than as a sum of regions or domains. 55 Although we were able to artificially create a more persistent IgE with V-regions that augmented FcεRIa engagement in the rare pertuzumab VH5 IgE (the only of 10 recombinant IgEs we produced), the discovery for such a patient-derived IgE would certainly change the understanding of the role of IgE V-regions in allergy pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since viruses can develop cross-resistance to multiple drugs [21,43], and Y183 has yet to have a reported clinical mutation, compound 2 serves as a potentially important guide for targeting drug-resistant HIV-1 variants, and with the conservation of the site across RTs -a possible broad-spectrum RTI as well. By taking a holistic approach [44] in studying the whole structure of the target proteins and looking for common sites and how resistance develops, as demonstrated for HIV-1 Gag [45], HIV-1 Protease [43], and antibodies [46][47][48][49][50][51], the search for common druggable conserved sites across protein families can add to the success of developing broad-spectrum therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric modulation has been an area of interest in molecular immunology (Janda et al, 2016;Lua et al, 2019;Su et al, 2017;Yang et al, 2017). Previous experimental and computational studies of IgG and IgA have suggested that the Fc and Fab regions of an antibody might communicate with one another Phua et al, 2019); for example, point mutations on the Fc region may reduce binding affinity, whilst antigen binding to the Fab region changes the conformation of the Fc domain to promote binding to its receptor (Lua et al, 2019;Oda et al, 2003;Schlessinger et al, 1975;Su et al, 2018). Allostery between the different subunits in a multimeric IgM, however, remain elusive.…”
Section: Discussionmentioning
confidence: 99%